Absorção de cádmio e zinco por Alternanthera tenella Colla (Amaranthaceae) e modificações anatômicas e fisiológicas - Rodrigues, Luiz Carlos de Almeida (2016)
Mining is one of the main activities related to soil contamination by cadmium (Cd) and zinc (Zn). The presence of unnatural concentrations of Cd in the environment has been recognized as a potential risk due to its nonbiodegradability and high toxicity. Zn is an essential nutrient for plant growth, but in high concentrations may exhibit phytotoxicity affecting plant development. Phytoremediation is presented as a good cost-effective and ecofriendly technique to recover degraded areas, which uses plants with tolerance and accumulation responses for trace elements. The study was performed to evaluate the tolerance and potential to accumulation of Alternanthera tenella Colla, which belongs to Amaranthaceae family and occurs in a degraded area of Zn mining in Vazante-MG. Anatomical and physiological analysis were performed on plants grown on Cd and Zn-contaminated soil in a green house and on a in vitro contaminated medium. We observed that A. tenella was able to uptake and translocate sufficient amount of Cd and Zn to be considered as hyperaccumulator species. Thus, the species have potential for application in phytoremediation processes. High Zn concentrations induced increased absorption of Cd, but reduced the toxic effects of this element by competition for binding sites on the plant. Due to the high Zn concentration compared to Cd, important anatomical changes were induced mainly by Zn, which promoted some phytotoxicity on gas exchange of the species. For the in vitro experiment, in turn, it became apparent competition between Cd and Zn absorption by A. tenella, which had its anatomical , antioxidant and growth features affected by high concentrations of Cd. In this condition, increased Cd content reduced Zn uptake by A. tenella. For both greenhouse and in vitro conditions, the anatomical changes were induced in order to promote the retention and prevent the translocation of the evaluated trace elements.